Fluorescent biosensors for high throughput screening of protein kinase inhibitors. Issue 2 (19th December 2013) - Prével, Camille; Pellerano, Morgan; Van, Thi Nhu Ngoc; Morris, May C.
Abstract High throughput screening assays aim to identify small molecules that interfere with protein function, activity, or conformation, which can serve as effective tools for chemical biology studies of targets involved in physiological processes or pathways of interest or disease models, as well as templates for development of therapeutics in medicinal chemistry. Fluorescent biosensors constitute attractive and powerful tools for drug discovery programs, from high throughput screening assays, to postscreen characterization of hits, optimization of lead compounds, and preclinical evaluation of candidate drugs. They provide a means of screening for inhibitors that selectively target enzymatic activity, conformation, and/or function in vitro. Moreover, fluorescent biosensors constitute useful tools for cell‐ and image‐based, multiplex and multiparametric, high‐content screening. Application of fluorescence‐based sensors to screen large and complex libraries of compounds in vitro, in cell‐based formats or whole organisms requires several levels of optimization to establish robust and reproducible assays. In this review, we describe the different fluorescent biosensor technologies which have been applied to high throughput screens, and discuss the prerequisite criteria underlying their successful application. Special emphasis is placed on protein kinase biosensors, since these enzymes constitute one of the most important classes of therapeutic targets in drug discovery.